2015
DOI: 10.1111/jgh.12897
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease comorbid with major depressive disorder: The pathological features and poor therapeutic efficacy

Abstract: This is the first study to demonstrate the clinical features and response to therapy of NAFLD patients comorbid with MDD. The comorbid state of MDD was associated with more severe histological liver steatosis and worse treatment outcomes in patients with NAFLD. Further investigations are required to develop new lifestyle modification programs that enable NAFLD patients with MDD to achieve the treatment goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
79
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 29 publications
(26 reference statements)
10
79
1
4
Order By: Relevance
“…They assessed a cohort of 567 North American patients with biopsy-proven NAFLD and demonstrated that subclinical and clinical depression were noted in 53 and 14% of NAFLD patients, respectively, Interestingly, depression was associated with more severe hepatocyte ballooning and patients with subclinical depression had a higher likelihood of having more severe portal fibrosis after adjusting for confounders (Youssef et al, 2013). These results are consistent with another recent study by Tomeno et al (2015), in which NAFLD patients comorbid with MDD were characterized by more severe histological steatosis and higher NAFLD activity score. Moreover, serum aminotransferase, GGT, ferritin, and hs-CRP were dramatically higher in the NAFLD patients with MDD than those without MDD.…”
Section: The Link Between Depression and Cldsupporting
confidence: 93%
See 1 more Smart Citation
“…They assessed a cohort of 567 North American patients with biopsy-proven NAFLD and demonstrated that subclinical and clinical depression were noted in 53 and 14% of NAFLD patients, respectively, Interestingly, depression was associated with more severe hepatocyte ballooning and patients with subclinical depression had a higher likelihood of having more severe portal fibrosis after adjusting for confounders (Youssef et al, 2013). These results are consistent with another recent study by Tomeno et al (2015), in which NAFLD patients comorbid with MDD were characterized by more severe histological steatosis and higher NAFLD activity score. Moreover, serum aminotransferase, GGT, ferritin, and hs-CRP were dramatically higher in the NAFLD patients with MDD than those without MDD.…”
Section: The Link Between Depression and Cldsupporting
confidence: 93%
“…For example, Tomeno et al (2015) compared the NAFLD clinical response within different stages of MDD, and suggested that NAFLD patients comorbid with MDD had poor response to the 48 weeks standard care for NAFLD. In particular, NAFLD patients with unstable MDD (not in full/partial remission) had severe resistance to the treatment (Tomeno et al, 2015).…”
Section: Implications For the Clinical Management Of Patients With Cldmentioning
confidence: 99%
“…Other investigators have shown that depression is also affected by many lifestyle factors such as eating, exercise, and sleeping [24]. Consequently, previous studies have indicated an association between depression and NAFLD including histological features [14]. Interestingly, we found a decrease in oxy-Hb concentration during tasks in NAFLD patients despite having CES-D scores similar to those of healthy controls.…”
Section: Discussionsupporting
confidence: 40%
“…Although some patients with non-alcoholic fatty liver disease (NAFLD) have depression in addition to a positive association between depression and liver histological severity of NAFLD [14], other studies have found no association between depression and NAFLD [5–6]. This discrepancy may result from differences in evaluation methods for depression.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pro-inflammatory cytokines MIF [19,29,57], GRO-α [29], MCP-1 [58] and EN-RAGE [19,29] have been shown to be altered in multiple studies. Similarly, the anti-inflammatory cytokine IL-1ra [14,19,29,59] and the coagulation or acute-phase proteins A2macro [24,60,61,62], factor VII [63], vWF [24,29] and ferritin [19,64,65,66,67,68,69] have also been repeatedly reported to be altered in depression patients. Although we found several immune-/inflammation-related enzymes to be altered in patients including AXL, CK-MB and MMP-3, these changes have not been previously reported in depression.…”
Section: Discussionmentioning
confidence: 99%